2013
DOI: 10.1186/1471-2458-13-636
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination coverage rates among adults before and after the 2009 influenza pandemic and the reasons for non-vaccination in Beijing, China: A cross-sectional study

Abstract: BackgroundTo optimize the vaccination coverage rates in the general population, the status of coverage rates and the reasons for non-vaccination need to be understood. Therefore, the objective of this study was to assess the changes in influenza vaccination coverage rates in the general population before and after the 2009 influenza pandemic (2008/2009, 2009/2010, and 2010/2011 seasons), and to determine the reasons for non-vaccination.MethodsIn January 2011 we conducted a multi-stage sampling, retrospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 23 publications
1
49
2
Order By: Relevance
“…S1), because the crystal structure of the receptor was recently published (31). The mimic peptide from influenza NP 111-121 (containing residues in common with a peptide from HCRT receptor 2 [34][35][36][37][38][39][40][41][42][43][44][45] was also found to be located on the surfaceexposed region of the influenza NP crystal structure (figs. S1 and S2 and movie S1), which may be relevant for antibody generation as demonstrated by another B cell epitope for influenza NP (32).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…S1), because the crystal structure of the receptor was recently published (31). The mimic peptide from influenza NP 111-121 (containing residues in common with a peptide from HCRT receptor 2 [34][35][36][37][38][39][40][41][42][43][44][45] was also found to be located on the surfaceexposed region of the influenza NP crystal structure (figs. S1 and S2 and movie S1), which may be relevant for antibody generation as demonstrated by another B cell epitope for influenza NP (32).…”
Section: Resultsmentioning
confidence: 97%
“…Because natural infections can trigger autoimmune disease through molecular mimicry (5) (for example, Sydenham chorea is the result of an immune response cross-reacting with similar proteins contained in the microbe, b-hemolytic streptococcus, and the human brain), we compared these three microbial sequence fragments from influenza for similarity to fragments contained in human HCRT ligand or the HCRT receptors (components of the neurotransmission pathway dysregulated in narcolepsy) using a Smith-Waterman alignment. From these three fragments, only the sequence of influenza NP 111-121 , "YDKEEIRRIWR," was found to be similar to (mimicked) a sequence from the first extracellular domain (N terminus) of HCRT receptor 2 [34][35][36][37][38][39][40][41][42][43][44][45] , "YDDEEFLRYLWR" (e value = 0.0061), and the corresponding domain of HCRT receptor 1 [27][28][29][30][31][32][33][34][35][36][37] , "YEDEFLRYLWR" (e value = 0.026) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Most estimates of vaccination intention tend to be much greater than actual vaccine coverage estimates during the 2009 H1N1 pandemic [29]. Although the Beijing government launched mass vaccination campaigns during the second wave of the pandemic, the influenza vaccination coverage rates were relatively low (21.8%) and did not increased significantly during the 2009 H1N1 pandemic [12]. For the above reasons, we can infer that the actual coverage of H7N9 vaccination will be much lower than our estimate of 59.5% in emergency mass-vaccination campaigns during an emergency.…”
Section: Variablesmentioning
confidence: 97%
“…During the 2009 H1N1 pandemic, pandemic influenza vaccination was first provided to priority populations (e.g., older adults, public servants in key positions, students, teachers and people with chronic diseases) and then other persons in Beijing, and it was proven to be an effective strategy in controlling epidemics [11]. Our previous study showed the vaccination coverage rate was relatively low within the general adult population of Beijing, and the perceptions of not expecting to contract influenza was the predominant barrier to influenza vaccination [12]. Although Beijing has only reported 37 laboratory-confirmed cases of influenza A (H7N9) and 11 deaths as of August 2017, a potential threat of H7N9 pandemic has always been in Beijing.…”
Section: Introductionmentioning
confidence: 99%
“…Beijing also conducted influenza A(H1N1)pdm09 vaccination campaigns during the pandemic period. 9 These programs were implemented in the absence of local data on influenza-associated mortality burden because there was concern that this novel virus could have substantial burden on the population's health. Influenza mortality burden data allow programs to determine the potential impact of influenza vaccination and inform investments in prevention strategies.…”
Section: Introductionmentioning
confidence: 99%